Prevalence of reproductive tract infections including sexually transmitted infections among married women in urban and peri-urban mid to low socioeconomic neighbourhoods of Delhi, North India: an observational study protocol. Issue 3 (18th March 2022) - Dhabhai, Neeta; Chaudhary, Ritu; Wi, Teodora; Mburu, Gitau; Chowdhury, Ranadip; More, Deepak; Chatterjee, Leena; De, Devjani; Kabra, Rita; Kiarie, James; Habib, Ndema; Dang, Arjun; et al.
Abstract : Introduction: The Global Health Sector Strategy on sexually transmitted infections (STIs), endorsed by the World Health Assembly in 2016 aims to end STIs as public health threat by 2030. WHO conducts global estimates of prevalence to monitor progress towards achieving the same. However, limited laboratory confirmed data exist of STIs and reproductive tract infections (RTIs) apart from few prevalence surveys among key populations and clinic-based reports, including in India. Syndromic approach is the cornerstone of RTI/STI management and to maximise the diagnostic accuracy, there is a need to determine the main aetiologies of vaginal discharge. This study aims to estimate the prevalence of common STIs and RTIs and their aetiological organisms in symptomatic and asymptomatic women living in the urban and peri-urban, mid to low socioeconomic neighbourhoods of Delhi, North India. Methods and analysis: A cross-sectional study will be conducted among 440 married women who participated in the 'Women and Infants Integrated Interventions for Growth Study (WINGS)'. Information on sociodemographic profile, sexual and reproductive health will be collected, followed by examination and collection of vaginal swabs for nucleic acid amplification tests to diagnose Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomonas vaginalis and microscopy to identify bacterial vaginosis and Candida albicans . Treatment will be as per the syndromic approach recommendations in the Indian National Guidelines. Data will be analysed to estimate prevalence, presence of symptoms and signs associated with laboratory confirmed RTIs/STIs using STATA V.16.0 (StataCorp). Ethics and dissemination: This study protocol has been approved by the ethics review committees of the WHO and Society for Applied Studies (SAS/ERC/RHR-RTI/STI/2020). Approval has been obtained by the WINGS investigators from SAS ethics research committee to share the contact details of the participants with the investigators. The findings will be published in peer-reviewed journals and disseminated through scientific conferences. Trial registration number: CTRI/2020/03/023954.